PENGARUH KOTORAN LARVA KUMBANG TANDUK (Oryctes rhinoceros) TERHADAP PERTUMBUHAN KELAPA SAWIT (Elaeis guineensis Jacq) PADA TBM-I - Said Mursal; Wardati Wardati; Ardian Ardian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The research aims to find out the effect of rhinoceros beetles larvae feces  (Oryctes rhinoceros) and get the best dosage on growth of palm oil (Elaeis guineensis Jacq.) in preproduced-1. This research was conducted at palm oil plantation of PTPN V Sei Galuh Pantai Cermin Village, Tapung District, Kampar Regency, Riau Province, that was arrange completely randomized design (RAL) non-factorial with 4 levels and replicated 4 times, so there are 16 experimental units. The dosage for treatment of O. rhinoceros larvae feces (K) consists of 0, 5, 10 and 15 kg per plant. The observed parameters were increase plant height, increase number of plant midribs, increase plant stem circumference, increase length of plant midribs and increase number of plant leaves.  The results of the research showed that the effect of O. rhinoceros larvae feces increased the growth of palm oil in preproduced-1, as seen on parameters ofincrease plant height, increase number of plant midribs, increase plant stem circumference, increase length of plant midribs and increase number of plant leaves. The treatment of O. rhinoceros larvae feces at dose 15 kg per plant showed the highest impact on increase plant height with 62.50 cm, increase number of plant midribs with 14.00 strands, increase plant stem circumference with 37.25 cm, increase length of plant midribs with 50.75 cm and increasenumber of plant leaves with 10.50 strands. Keywords:Organic fertilizer of O. rhinoceros larvae feces, palm oil.